Predictive Value of NT-proBNP for Functional Outcome of Ischemic Stroke Without Cardiac Disease: A Prospective, Observational Study - Liu R; Chen G; Zhao N; Yue W (Neuropsychiatric Disease and Treatment)
Ran Liu,1 Guojuan Chen,2 Na Zhao,1 Wei Yue1 1Department of Neurology, Clinical College of Neurology, Neurosurgery and Neurorehabilitation, Tianjin Medical University, Tianjin Huanhu Hospital, Tianjin, 300350, People’s Republic of China; 2Department of Neurology, Tangshan Gongren Hospital, Tangshan, People’s Republic of ChinaCorrespondence: Wei Yue, Department of Neurology, Clinical College of Neurology, Neurosurgery and Neurorehabilitation, Tianjin Medical University, Tianjin Huanhu Hospital, No. 6 Jizhao Road, Shuanggang Town, Jinnan District, Tianjin, 300350, People’s Republic of China, Email hhyuewei2021@163.comPurpose: Our study aimed to evaluate the prognostic value of NT-proBNP in predicting adverse outcomes among patients with anterior circulation infarction (ACI) and posterior circulation infarction (PCI), specifically in those without pre-existing cardiac comorbidities.Patients and Methods: This single-center, prospective observational study enrolled patients with acute ischemic stroke (AIS) within 7 days of symptom onset. We aimed to elucidate predictive role of NT-proBNP levels in determining adverse outcomes in AIS patients. Additionally, the study sought to explore the relationship between NT-proBNP levels and the risk of poor functional outcomes in both ACI and PCI patients without underlying cardiac comorbidities.Results: A total of 821 patients were included in our study. Both univariate and multivariate logistic analyses indicated that higher NT-proBNP was an independent risk factor for adverse outcomes of ischemic stroke patients at 90 days. In noncardiogenic patients, the risks of adverse outcomes during follow-up were significantly elevated in the medium and high NT-proBNP groups (medium group: OR 1.75, 95% CI 1.03– 2.98, P=0.039; high group: OR 2.46, 95% CI 1.30– 4.67, P=0.006), with a dose-dependent trend. The association was similarly observed in patients with isolated ACI (medium group: OR 2.02, 95% CI 1.06– 3.83, P=0.031; high group: OR 2.70, 95% CI 1.25– 5.79, P=0.011). High NT-proBNP levels were independently associated with END in patients without underlying cardiac comorbidities (high group: OR 2.14, 95% CI 1.06– 4.31, P=0.033) and this association was also observed in ACI patients (high group: OR 5.39, 95% CI 1.70– 17.04, P=0.004). Moreover, when incorporated into the clinical prediction model, NT-proBNP exhibited excellent sensitivity and specificity for predicting stroke-related functional outcomes.Conclusion: NT-proBNP demonstrates potential as a valuable biomarker in the clinical predictive model for functional outcomes specifically in ACI patients suggesting that elevated NT-proBNP levels in these patients should prompt closer monitoring and more comprehensive patient management.Trial Registration: https://www.chictr.org.cn/, ChiCTR2300067696.Keywords: NT-proBNP, anterior circulation infarction, posterior circulation infarction, functional outcomes